Development of Wordless Comic Media For Learning Speaking Class V Primary School Students - Yulita, Yulita; Sayco, Sonia Castro Cuba; Neto, Antônio Justiniano Moraes (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
This research aims to develop wordless comic media as a speaking learning tool for fifth grade elementary school students. The development method used is Research and Development (R&D) with stages including preliminary study, planning, development, testing, evaluation and revision. Evaluation is carried out through observation, interviews, and speaking ability tests before and after using comic media. Revisions are carried out based on evaluation results to improve and improve the quality of comic media. The research results show that the use of wordless comic media can increase students' interest in learning to speak. Students demonstrate increased ability to convey ideas, understand context, and communicate effectively. This comic media also helps students who have difficulty understanding written texts. In conclusion, the development of wordless comic media can be an effective alternative in teaching speaking in fifth grade elementary school. Support from the teacher is needed in implementing this media so that it can provide maximum benefits for the student learning process.